IMPLEMENTASI SOP PELAYANAN DI DINAS KOPERASI, USAHA MIKRO KECIL MENENGAH, PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN PESISIR SELATAN - Ramadhan, Rizki Mandala (Jurnal Teori dan Riset Administrasi Publik, 2024)
Rizki Mandala Ramadhan, 1410842015, Implementation of SOP Services at the Office of Cooperatives, Micro, Small and Medium Enterprises, Trade and Industry, Pesisir Selatan Regency, Department of Public Administration, Faculty of Social and Political Sciences, Andalas University, Padang, 2021. Supervised by: Kusdarini, S. IP, M.PA and Dr. Ria Ariany, M.Si. This thesis consists of 156 pages with references to 8 theory books, 4 method books, 2 journals, 1 Thesis, 5 Regulations and 1 appendix. There are employees who do not understand or do not understand the contents of the existing Service SOP. In addition, there are also employees who work not according to the rules in the SOP, this is because the behavior and background of the employee who initially did not work according to the rules. The lack of ability of employees in using service support facilities such as computers and printers results the services provided are not optimal. Competence is indeed a fundamental problem in the service process carried out, especially competencies related to the use of service support facilities. So that the formulation of the problem in this study is "How is the Implementation of the Service SOP at the Department of Cooperatives, Micro, Small and Medium Enterprises, Trade and Industry in Pesisir Selatan Regency." This study aims to describe the Implementation of the Service SOP in the Office of Cooperatives, Micro, Small and Medium Enterprises, Trade and Industry in Pesisir Selatan Regency using Edward III's theory. Aspects that are reviewed from Edward III's theory include aspects of communication, resources, disposition and bureaucratic structure. This study uses a qualitative approach with a descriptive type of research. The data collection technique is through interviews and documentation, while the data validity technique uses a source triangulation process. As for the conclusions in this study, the Implementation of SOP Services in the Office of Cooperatives, Micro, Small and Medium Enterprises, Trade and Industry in Pesisir Selatan Regency is not optimal. Low employee competence related to the services provided. The lack of supporting facilities for the implementation of services, especially facilities related to technology such as computers and printers. There are employees who have a low response to the service orders given. Lack of awareness that employees have of their duties in providing services. The first suggestion in this research is to improve the quality of human resources such as the implementation of employee competency training so that the services provided to the community can be better in the future. Second, increasing the number of supporting facilities related to the services provided, especially facilities related to technology, namely computers and printers. Third, optimizing supervision of the services provided, both direct supervision (providing direct direction to employees related to their duties) and indirect supervision (providing direction through the head of the field/sectional head regarding employee duties) as a form of authority in the service process.